Neopestalotiopsis spp., an invasive fungal pathogen, is a major threat to strawberry production: the current status, challenges, and future directions - Gaire, Susmita; Muzhinji, Norman; Louws, Frank J.; Adhikari, Tika B. (Frontiers in Plant Science, 2026)
Pestalotioid fungi have traditionally been regarded as secondary or opportunistic pathogens of strawberries, which has led to limited research attention. However, recent outbreaks of Neopestalotiopsis have demonstrated its potential to act as a primary pathogen, posing a significant threat to strawberry production worldwide. Current management strategies primarily involve propagation of pathogen-free plants, cultural practices such as field sanitation, crop rotation, and the removal of infected plants, supplemented by the application of biocontrol agents and fungicides. Advances in molecular diagnostic tools have improved early detection and monitoring of Neopestalotiopsis spp. Furthermore, initial efforts have begun to identify sources of genetic resistance in strawberry, thereby supporting future breeding programs. Despite these advancements, a considerable gap remains in our understanding of the host’s defense mechanisms, the pathogen’s infection strategies, the dynamics of their interactions, and the pathogen’s ecology. The taxonomy’s complexity and the variability in virulence among its isolates further complicate diagnosis and control efforts. Addressing these challenges is crucial to developing sustainable, integrated disease management strategies and advancing resistance breeding, thereby ensuring the long-term productivity and resilience of the strawberry industry. This review consolidates the current understanding of Neopestalotiopsis spp., evaluates the available diagnostic tools and management strategies, discusses recent progress in genetics and genomics for breeding resistance to this pathogen, and identifies areas for further research.